Media Framing and the Legitimazation of Sharia in Aceh: An Analisys of Serambinews.com - Azman Sulaiman; Lahmuddin Lubis; Zulkarnain Abdurrahman; Nanda Putri (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Digital advances have revolutionised communication patterns and the formation of opinion, including perceptions of Islamic law. In Aceh, which has formally implemented Islamic law for over 23 years, the dynamics of online media reporting have become a crucial factor in shaping its image and the construction of religious identity. This article analyses the role of Serambinews.com in framing news coverage about Islamic law in Aceh. From 9 articles found via a search using the keyword “Syariat Islam” on the site, 7 articles met the inclusion criteria as factual news reports and were analysed using Entman’s framing model (problem definition, causal interpretation, moral evaluation, treatment recommendation). The seven articles were purposely selected from the period of November 2024. This period was chosen based on the intensity of reporting related to the evaluation of sharia implementation after more than 23 years. While existing studies have discussed media representation of Islamic law in Indonesia, limited attention has been paid to how local online media in Aceh construct framing that legitimizes sharia enforcement. This study specifically addresses that gap by offering a systematic framing analysis of Serambinews.com. The results indicate that Serambinews.com consistently frames Islamic law as a solution for moral and social order. The legitimacy of its implementation is affirmed through narratives highlighting broad public support, claims of tolerance from interfaith figures, and institutional collaboration with educational bodies. The reporting tends to present a singular narrative without critical views, which contributes to the discursive construction of Sharia as a legitimate public norm in Aceh. However, given the limited empirical scope (seven articles from one outlet over one month) these findings should be interpreted with caution and are not generalizable to all local media in Aceh.